APAKAH RISIKO DETERMINAN BAGI KINERJA BANK PERKREDITAN RAKYAT? - Mychelia Champaca; Moch Nurhidayat; Rizalnur Firdaus (Media Mahardhika, 2023)
Most of the studies on risk relationships have been carried out in the context of commercial banking, and only a few have examined microfinance. This study seeks to raise the issue of risk-taking as a form of bank behavior tested in the context of microfinance. Due to the high risk and the spread of the number of branch offices, which are very wide and numerous compared to commercial banks or other microfinance institutions, this study examines the risks to microfinance performance using rural banks data as a formal form of microfinance representation. This study uses all rural bank data in Indonesia in examining the role of risk in rural banks profitability and efficiency performance. Risk indicators used in testing include liquidity risk, solvency risk, and credit risk. The findings of this study show that risk reduces profitability, reduces efficiency, and reduces credit repayments. The test results indicate that the role of the Indonesian government through its policies shows good control over risk management in microbanking to prevent contagion effects that lead to systemic risk due to the wide reach of rural banks.